2013
DOI: 10.1002/dev.21160
|View full text |Cite
|
Sign up to set email alerts
|

Development of auditory event‐related potentials in infants prenatally exposed to methadone

Abstract: Developmental features of the P2 auditory ERP in a change detection paradigm were examined in infants prenatally exposed to methadone. Opiate dependent pregnant women maintained on methadone replacement therapy were recruited during pregnancy (N = 60). Current and historical alcohol and substance use, SES, and psychiatric status were assessed with a maternal interview during the third trimester. Medical records were used to collect information regarding maternal medications, monthly urinalysis, and breathalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In another cohort study of children aged 1 to 8.5 years (POE/polysubstance exposed versus unexposed controls), sex-specific outcomes were found, with decreased cognitive scores in exposed boys at age 3, and lower functioning among exposed girls emerging over time [13]. However, the study had numerous limitations, including recruitment from a social service institution for high-risk children where most of exposed children did not live with biological parents, reliance on medical records and maternal report (when available) to obtain information on prenatal exposures, and non-blinded assessments of the outcomes [13, 35]. Attempts to compare the effects of different prenatal MAT regimens (methadone vs. buprenorphine and dose levels) on neurodevelopment have yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort study of children aged 1 to 8.5 years (POE/polysubstance exposed versus unexposed controls), sex-specific outcomes were found, with decreased cognitive scores in exposed boys at age 3, and lower functioning among exposed girls emerging over time [13]. However, the study had numerous limitations, including recruitment from a social service institution for high-risk children where most of exposed children did not live with biological parents, reliance on medical records and maternal report (when available) to obtain information on prenatal exposures, and non-blinded assessments of the outcomes [13, 35]. Attempts to compare the effects of different prenatal MAT regimens (methadone vs. buprenorphine and dose levels) on neurodevelopment have yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Even with a successful labor and delivery, neonates often have low birthweight and smaller head circumference as well as experience symptoms of opiate withdrawal (Binder and Vavrinkova, 2008;Hunt et al, 2008;Kandall et al, 1976). Some clinical studies have also suggested an increased prevalence of heart defects, autonomic dysregulation (Paul et al, 2014), nystagmus (Gupta et al, 2012), and strabismus (Gill et al, 2003) in children exposed prenatally to opiates. At the pre-and elementary school ages, these children show motor and cognitive impairments (Bunikowski et al, 1998;Guo et al, 1994;Hunt et al, 2008), inattention (Hickey et al, 1995;Ornoy et al, 1996), hyperactivity (Ornoy et al, 1996), and an increase in ADHD when exposed prenatally to heroin (Ornoy et al, 2001).…”
Section: Opioidsmentioning
confidence: 99%
“…Even though methadone reduces symptoms compared with illicit opiate use, clinical cohorts have demonstrated that prenatal methadone exposure can lead to increased premature birth (Cleary et al, 2012;FajemirokunOdudeyi et al, 2006;Lejeune et al, 2006), decreased birthweight (Cleary et al, 2012;Hulse et al, 1997;Kandall et al, 1976;Sarfi et al, 2009;, and smaller head circumference (Brown et al, 1998;Hans, 1989;Rosen and Johnson, 1985;Welle-Strand et al, 2013;Wilson et al, 1981). Additional reports indicate an increased incidence of respiratory insufficiency at birth (Maas et al, 1990), altered corrected QT interval on electrocardiogram during the first postnatal week (Parikh et al, 2011), postnatal hyperphagia (Martinez et al, 1999), disrupted auditory event related potentials (Paul et al, 2014), and myelination deficits (Walhovd et al, 2012). However, the prevalence of cognitive impairments produced by prenatal methadone has been questioned because some studies have not observed differences in cognitive development (de Cubas and Field, 1993;Hans, 1989;Rosen and Johnson, 1985) or performance (Bauman and Levine, 1986;Soepatmi, 1994;van Baar, 1990;van Baar and de Graaff, 1994;.…”
Section: Methadonementioning
confidence: 99%
“…Unfortunately, Maine (Alexander et al, 2004;Brown et al 2015;Grau et al, 2007;Heimer et al, 2012;Martin & Rocque, 2011;McCall et al, 2013;Roche, 2000;Rosenberg, 2002;Sorg & Greenwald, 2003) has played a prominent role in this national opioid epidemic (Center for Behavioral Health Statistics and Quality, 2015;Johnston et al, 2015;Maxwell, 2011;Patrick et al, 2015;Paul et al, 2014;Warner et al, 2011). The total daily opioid dose in morphine equivalents in the United States was highest in Maine (798 mg/person), which was approximately fourfold higher than that in the lowest state.…”
mentioning
confidence: 99%